Hypoglycaemia-induced Parkinsonism in a Patient with Diabetes Mellitus and Tuberculous Encephalitis: A Complex Case Report - Venkatramani Padma; Pusapati Lakshmi Chaitanya Varma; Sathyapriya; Mathisha Ebby Perin; Ishai Vannan (Journal of Clinical and Diagnostic Research)
Hypoglycaemia-induced Parkinsonism is a rare but significant complication of metabolic brain dysfunction, characterised by movement disorders following severe hypoglycaemia. We present a 65-year-old male with a 12-year history of type 2 diabetes mellitus, Autoimmune Haemolytic Anaemia (AIHA), and recent tuberculous encephalitis who was found unresponsive due to severe hypoglycaemia. Despite intravenous glucose administration, he developed new-onset Parkinsonism, manifesting as tremors, rigidity, and bradykinesia. Neurological imaging revealed hippocampal involvement on Magnetic Resonance Imaging (MRI), while a Dopamine Transporter (DaT) scan demonstrated reduced striatal uptake, confirming a dopaminergic deficit. The patient was managed with basal-bolus insulin therapy, corticosteroids for AIHA, and anti-tubercular treatment, while Parkinsonian symptoms improved with levodopa/carbidopa, trihexyphenidyl, and amantadine. Hypoglycaemia-induced neuronal injury results from metabolic failure, oxidative stress, excitotoxicity, and neuroinflammation, leading to selective neuronal necrosis, particularly affecting the basal ganglia, hippocampus, and substantia nigra. While some cases demonstrate reversible outcomes due to vasogenic oedema, others progress to irreversible neurodegeneration, emphasising the need for stringent glycaemic management and early recognition of neurological sequelae in diabetic patients.